RISK FACTORS OF CATARACT IN TYPE 2 DIABETES MELITUS - Ahmad Fauzi; Soeharyo Hadisaputro (Fakultas Kedokteran Universitas Lampung, 2014)
Background: One of Diabetes Melitus (DM) complication to the eye that may result as visual disturbances and blindness is cataract. According to The Framingham Eye Study and the Health and Nutrition Examination Survey shows that patient with DM before age of 65 years is easier 3-4x to get cataract and 2x easier than the age after 65 years compared to non DM. The research about risks factors for diabetic cataract in type 2 DM in Indonesia is rare, so that it is necessary to do the research about these risk factors. Method: This study involves observational analytic study with case control study design. Subject of the case is type 2 DM with cataract (73 people) and type 2 DM without cataract as control (73 people) at Dr. Kariadi Hospital Semarang. Then data followed retrospectively about risk factors that influence incidence of cataract in type 2 DM. The stages of analysis used in this study is univariate analysis, bivariate analysis and multivariate analysis. The statistics test used in multivariate analysis is Multiple Logistic Regression. Result: The multivariate analysis shows that 5 years Duration of DM or longer (P=0,002) and Trigliserida value ≥150 mg/dl (P=0,015) are the risks factors for cataract in type 2 DM. Conclusion: 5 years duration of DM or longer and trigliserida value ≥150 mg/dl are factors that proven as risk factors for cataract in type 2 DM. [Juke Unila 2014; 4(8):173-179]